Three new species of the barracudina genus Lestidium (Aulopiformes: Paralepididae) from the Indo-West Pacific - Ho, Hsuan-Ching; Graham, Ken; Russell, Barry (Zootaxa, 2020)
Three new species of the genus Lestidium with complete lateral line are described from the Indo-west Pacific Ocean. Lestidium longilucifer sp. nov., from Western Australia and Taiwan, belongs to the Lestidium atlanticum species complex and can be separated from other congeners by having 41–43 prehaemal vertebrae, 85–88 total vertebrae and 126–146 total lateral-line scales; and body proportions. Lestidium australis sp. nov. from eastern Australia and Lestidium rofeni sp. nov. from Taiwan and the Philippines together with Lestidium prolixum form the L. prolixum species complex. These three species can be separated from each other by a combination of different fin positions, vertebral formula, number of lateral-line scales and pigmentation.